Photodynamic Therapy: A Novel Ally for Surgical Endodontic Treatment? Case Report - Oliveira, Bruna Paloma de; Câmara, Andréa Cruz; Ferreira, Glauco dos Santos; Neto, Sebastião Pedro Santos; Silva, Patrícia Fernandes Cassimiro da; Aguiar, Carlos Menezes (Journal of Lasers in Medical Sciences, 2018)
Introduction: Photodynamic therapy (PDT) has emerged as a powerful tool for conventional endodontic treatment, capable of eradicating microorganisms present in endodontic infections. Despite this, the use of PDT in the surgical endodontic treatment is not well-known. Case Report: This paper describes the case of a patient with asymptomatic apical periodontitis in a mandibular incisor submitted to surgical endodontic treatment associated with PDT. After conventional procedures, photosensitizer methylene blue (0.01%) was applied to the retrograde cavity for 3 minutes, followed by irradiation with diode laser (100 mW and 660 nm) for 3 minutes. Six months after the procedure, the patient was asymptomatic, and the radiographic examination showed healthy periradicular tissues. Conclusion: The association of PDT with surgical endodontic treatment was effective, suggesting that this therapy may provide additional benefits to patients when compared to the conventional surgical technique.